The Turning Ideas into Stories: Enhancing Elementary Students' Fiction Writing through the Time Token Arends Model and Flipaclip Media - Retno Maharani, Diva; Yulisetiani, Septi (Jurnal Ilmiah Sekolah Dasar, 2025)
Writing problems are still commonly experienced by elementary school students, especially difficulties in generating ideas and developing structured stories due to suboptimal learning processes. Therefore, an innovative learning model is needed to help students develop ideas and compose stories in a more directed manner to improve their writing skills. This study aims to analyze the effect of implementing the Time Token Arends learning model assisted by Flipaclip media on the fiction story writing skills of elementary school students. This research is a quantitative study using an experimental method with a quasi-experimental nonequivalent control group design. The sample consisted of 62 fifth-grade elementary school students selected through simple random sampling. Data collection was carried out using essay tests through pretest and posttest. Data were analyzed using the independent sample t-test. The results showed a Sig. (2-tailed) value of 0.001 < 0.05, indicating a significant difference in the posttest mean scores between the experimental and control groups. Students in the experimental group demonstrated improved ability to develop ideas into coherent writing, as indicated by the completeness of story elements, proper grammar usage, and a well-structured and chronological storyline. It can be concluded that learning using the Time Token Arends model assisted by Flipaclip media positively influences the fiction story writing skills of fifth-grade elementary school students.